Clinical management of a severe traumatic cutaneous myiasis at the base of the antler in a fallow deer, Dama dama: A case report - Wan Jaafar, Wan Nor Fitri; Rashid, Muhammad Azrolharith; Abdullah, Faez Firdaus Jesse; Lim, Eric Teik Chung; Mohd Azmi, Mohd Lila; Salleh, Annas; Zamri, Zulfakarudin; Hisham, Azrul; Che Ali, Aznida; Haron, Abd Wahid; Baiee, Falah Hasan Ali (University of Mosul - College of Veterinary Medicine, 2021)
Cutaneous myiasis is the infestation of larvae of flies in the vertebrate. The condition causes significant economic losses to the livestock industry indicating the importance of a systematic approach to clinical management. The incidents of two episodes of severe cutaneous myiasis wound at the base of the antler in a 5-year-old semi-intensively managed male Dama dama deer was described. Physical examination revealed a foul-smelling necrotic wound around the left cornual region measuring 5cm×4cm in radius and 3cm in depth and fly eggs were seen on the surface of the wound. The clinical findings suggest the diagnosis of a severe cutaneous myiasis. The case was managed by wound debridement and flushing with hydrogen peroxide 3% and diluted hibiscrub 0.05%, followed with povidone iodine 2.5%. Topical ointment, Dermapred® and insecticide, Negasunt® were applied topically. Parenteral administration of flunixin meglumine 2.2 mg/kg for 3 days and Oxytetracycline 1 ml/10 k every 72 hours, given twice both through intramuscular route. Supplement injections, Vitavet® and Catosal™ were given to improve the wound healing process. The outcome of the wound improved post-14 days of treatment. Administration of timely combination of antimicrobials, pain management and flies control are leading factors to a good healing process.